45 Decision support and knowledge translation tools to highlight the benefits and harms of screening: an analysis of online access and dissemination of the canadian task force for preventive healthcare resources. (20th August 2018) - Lang, Eddy; Kasperavicius, Danielle; Buckland, Danica; Scoleri, Rossella; Moore, Julia E; Thombs, Brett; Straus, Sharon
Abstract : Objectives: The Canadian Task Force for Preventive Healthcare (CTFPHC) has developed a bilingual library of fifteen tools to support clinical and shared decision-making for screening in primary care. https://canadiantaskforce.ca/tools-resources/. These include clinical algorithms and frequently asked questions as well as infographics that are designed to facilitate Knowledge Translation (KT). We report the proportion of guidelines in the CTFPHC library which recommend against screening based on harms such as overdiagnosis. We also set out to describe the access and dissemination metrics for these resources from both language and geographical perspectives as well as in terms of inter-resource comparisons. Method: Resources include clinical and patient algorithms, clinician and patient FAQs and infographics that are designed to communicate harms and benefits including over-diagnosis and false positive estimates. Resources were developed with input from clinicians and patients. We examined website access and report on dissemination strategies for CTFPHC KT tools using website analytics as well as data on from the Canadian Medical Association Journal (CMAJ). Results are reported descriptively for the years 2016 and 2017 inclusively. Results: Most CTFPHC guidelines (11/15) recommend against screening. The most widely viewed were the clinical algorithm for Hypertension and the '1000 person tool' for prostate cancer which highlights harms and benefits. English versions were viewed approximately 7000 times each in 2016 and 2017 with the French version accessed at 10% of that. Childhood obesity, developmental delay and cognitive impairment screening were among the least viewed with approximately 700 total views in English (2016/2017). In 2017, 70 000 hard copies of KT tools for abdominal aortic aneurysm, Hepatitis C screening and tobacco smoking in children and adolescents were distributed with the CMAJ. City-based analysis of access in Canada is in keeping with population levels with the exception of Ottawa where the CTFPHC is based and was ranked third. Both in 2016 and 2017, Brazil logged the third most sessions with the CTFPHC website after Canada and the US. Conclusions: The CTFPHC guidelines highlight the harms of screening by demonstrating rates of overdiagnosis and have recommended against screening in controversial areas such as breast cancer screening for women aged 40–49 and colon cancer screening for men aged greater than 75; colonoscopy is also recommended against as a screening tool. The CTFPHC resources to support decision-making receive modest online traffic. The screening scenario for which the harms likely outweigh the benefits i.e. prostate cancer screening are among the most widely seen. These resources are accessed beyond the intended Canadian audience.